2017
DOI: 10.1111/arcm.12300
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Alteration of Lithic Artefacts: an Experimental Case Study on the effect of Guano on Stone Flakes and Its Contextualization in the Archaeological Assemblage of Azokh Cave (Southern Caucasus)

Abstract: Chemical weathering of archaeological material is well known; however, while there have been a number of experimental studies demonstrating different types and degrees of chemical alteration on faunal remains, little attention has been paid to stone tools, and the few studies that exist relate mainly to siliceous materials and water‐induced chemical alteration. Azokh Cave, located in the South Caucasus, contains a Middle Pleistocene to Holocene infill, and detailed macro‐ and microscopic examination of the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Nevertheless, the effects of weathering on lithic artefacts are not easy to predict. They vary by both artefact mineralogy and environmental conditions, including the geochemical properties of the sedimentary deposits 18 21 , the combination of which can result in highly selective and differentiated modes of attack during the taphonomic processes. The basic assumption that fine grained flint resist weathering better than coarse grained one 20 , and the recognition that most of the strongly weathered artefacts (Group 1) are made on medium-coarse grained flint, whereas fine and very fine grained flint artefacts show a good preservation of edges and ridges, lighter surface alteration and little to no patination (Groups 2 and 3), significantly narrows down the seeming heterogeneity and suggests the likelihood that the observed differential alteration largely depended on raw material type.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the effects of weathering on lithic artefacts are not easy to predict. They vary by both artefact mineralogy and environmental conditions, including the geochemical properties of the sedimentary deposits 18 21 , the combination of which can result in highly selective and differentiated modes of attack during the taphonomic processes. The basic assumption that fine grained flint resist weathering better than coarse grained one 20 , and the recognition that most of the strongly weathered artefacts (Group 1) are made on medium-coarse grained flint, whereas fine and very fine grained flint artefacts show a good preservation of edges and ridges, lighter surface alteration and little to no patination (Groups 2 and 3), significantly narrows down the seeming heterogeneity and suggests the likelihood that the observed differential alteration largely depended on raw material type.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have also found etching of calcite crystals resulting from limestone heating [22]. Experiments with burying in guano, which can have saline and acid effects, have described reactivity of lithologies with calcium phases in limestone and basalt [9]. According to Deng et al [36], clay minerals can react with acid solutions, enhancing the microporosity and susceptibility to freeze-thaw of sandstones.…”
Section: Minerals and Other Phase Constituentsmentioning
confidence: 99%
“…Asryan et al 2014;Burroni et al 2002;Michel et al 2019;Newcomer 1976;Sala 1986;Thiébaut 2007). Chemical processes, such as those related to soil chemistry or weathering, may alter or obliterate wear traces, as these processes may lead to surface patination, gloss or polish formation (Asryan et al 2017;Plisson and Mauger 1988;Rottländer 1975). Also, thermal modifications, being the result of (unintentional) exposure to heat or freeze-thaw actions, have to be taken into account when evaluating post-depositional wear and other wear (e.g.…”
Section: Introductionmentioning
confidence: 99%